A label-free "turn-on" fluorescence platform for glucose based on AuNCs@MnO2 nanocomposites. (5th August 2019) - Liu, Shimeng; Lv, Changyin; Liu, Ran; Yang, Guiying; Li, Shiya; Zuo, Li; Xue, Panpan
Abstract : The principle of sensitive detection of glucose in human serum using Bro-AuNCs @MnO2 nanocomposites as a fluorescent sensor. Abstract : Diabetes mellitus is a lifelong chronic metabolic disease; it poses a serious threat to human health. Blood glucose measurement is one of the most important tests for diagnosing diabetes. Therefore, establishing an accurate and reliable method for determining glucose levels in serum is still of great significance. In this work, a novel fluorescent sensing platform using gold nanoclusters (AuNCs) and MnO2 nanocomposites as fluorescent probes was designed for the detection of glucose. First, gold nanoclusters (Bromelain-AuNCs) were synthesized by using bromelain as a template. MnO2 nanosheets were added to the system, and stable AuNCs@MnO2 nanocomposites were formed in 5 min. The fluorescence was quenched due to the inner filter effect (IFE) and static quenching effect (SQE) in the system. However, in the presence of H2 O2 produced by an enzymatic reaction of glucose oxidase (GO x ), the MnO2 nanosheets are reduced to Mn 2+ ions, releasing AuNCs. At this point, the fluorescence is restored in the system. Therefore, the glucose concentration can be indirectly detected from the H2 O2 produced by the glucose oxidase enzymatic reaction. For glucose detection, the broad linear range of this method is 25 μmol L −1 to 30 mmol L −1 and the detection limit is 6.7 μmol L −1 . The practical application of the system is demonstrated in human blood samples. Compared with the whole-blood automatic analyser, this method showed satisfactory results.